Genealogies of music and memory Gluck in the 19th-century Parisian imagination - Everist, Mark 1956- (Oxford University Press, 2021)
The history of music is most often written as a sequence of composers and works. But a richer understanding of the music of the past may be obtained by also considering the afterlives of a composer's works. 'Genealogies of Music and Memory' asks how the stage works of Christoph Willibald Gluck (1714-1787) were cultivated in nineteenth-century Paris, and concludes that although the composer was not represented formally on the stage until 1859, his music was known from a wide range of musical and literary environments
Enthält bibliographische Angaben und Index
Keywords: Gluck, Christoph Willibald / Ritter von / 1714-1787 / Operas; Gluck, Christoph Willibald / Ritter von / 1714-1787 / Performances / France / Paris / History / 19th century; Gluck, Christoph Willibald / Ritter von / 1714-1787 / Appreciation / France / Paris / History / 19th century; Gluck, Christoph Willibald -- 1714-1787; Geschichte 1820-1859; Geschichte 1770-1870; Opera / France / Paris / 19th century; Oper; Aufführung; Rezeption; Paris